Salvage contributions : prairie provinces - Wilmeth, R. (Mercury series., 1975)
Reports on work at the Stendall site (C3-Wa-1), Manitoba; Upper Highwood and Elbow river basins, Alberta; St. Mary and Belly River regions; S.S. Burmis site (DjPn-62); Chipman river survey, Saskatchewan; and Bakken-Wright site, Saskatchewan.